Management features of Erasmus+ International Credit Mobility Project in the conditions of war - A.S. Polianska (Економіка, управління та адміністрування)
Academic mobility is one of the best and most effective instruments for raising the quality of education and competitiveness among higher educational institutions. During the last 18 years, after joining the Bologna process in 2005 and recognizing the mobility as one of the strategies on the way of building the European space of higher education, Ukraine became responsible for reforming the national system of education due to its active position in international academic mobility programs implementation. The article reveals the notion and types of academic mobility among Ukrainian students. The article reviews the context and basic statements of normative legal documents, regulating the academic mobility realization as one of the internationalization components of higher education. Broad opportunities for participation in academic mobility exchanges are available for Ukrainian students due to the European Union Erasmus+ Program, the International Credit Mobility Project. It is a significant step ahead in the process of The Law of Ukraine «On Higher Education» execution and the development of effective instrument for internationalization of Ukrainian higher educational institutions. The article reviews the basic principles for international academic mobility project implementation at Zhytomyr Polytechnic State University and makes the analysis of contemporary international academic mobility conditions during the war.